Androgen deprivation and androgen receptor competition by bicalutamide induce autophagy of hormone‐resistant prostate cancer cells and confer resistance to apoptosis123. Issue 10 (26th March 2013) - Boutin, Benoît; Tajeddine, Nicolas; Vandersmissen, Patrick; Zanou, Nadège; Van Schoor, Monique; Mondin, Ludivine; Courtoy, Pierre J.; Tombal, Bertrand; Gailly, Philippe
Abstract BACKGROUND Treatment of advanced prostate cancer (PCa) relies on pharmacological or surgical androgen deprivation. However, it is only temporarily efficient. After a few months or years, the tumor relapses despite the absence of androgenic stimulation: a state referred to as hormone‐refractory prostate cancer (HRPCa). Although autophagy confers chemoresistance in some cancers, its role in the development of HRPCa remains unknown. METHODS Autophagic flux was assayed by GFP‐LC3 clustering, by LC3‐I to LC3‐II conversion and transmission electron microscopy. Cell death was detected by sub‐G1 quantification and concomitant measurement of transmembrane mitochondrial potential and plasma membrane permeabilization. Inhibition of autophagy was achieved by siRNAs and pharmacological inhibitors. RESULTS Androgen deprivation or treatment with the anti‐androgen bicalutamide promoted autophagy in HRPCa‐derived LNCaP cells. This effect was dramatically reduced after depletion of Atg5 and Beclin‐1, two canonical autophagy genes, and was associated with an inhibition of the androgen‐induced mTOR pathway. The depletion of Atg5 and Beclin‐1 significantly increased the level of cell death induced by androgen deprivation or bicalutamide. Finally, the safe anti‐malarial drug chloroquine, an inhibitor of autophagy, dramatically increased cell death after androgen deprivation or bicalutamide treatment. CONCLUSION Taken together, our data suggest that autophagy is a protective mechanism against androgen deprivation in HRPCa cells and that chloroquine could restore hormone dependence. This set of data could lead to the development of new therapeutic strategy against HRPCa. Prostate 73: 1090–1102, 2013. © 2013 Wiley Periodicals, Inc.